2020
DOI: 10.1108/ijdig-11-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

HRM practices and innovation: an empirical systematic review

Abstract: Purpose The relationship between human resource management practices (HRMP) and innovation has been described as a black box, where a lot still needs to be investigated. Thus, the aim of this paper is to investigate the nature of the link that exists between HRMP and innovation in both public and private organizations. To do so, theoretical underpinnings and existence of a mediating or a moderating mechanism is inspected. Design/methodology/approach Based on an empirical systematic review of research conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 51 publications
(145 reference statements)
2
33
0
2
Order By: Relevance
“…The financial results are measured, for example, by means of market share, profits, sales, financial liquidity, share price, firm value and company’s goodwill (Arthur, 1994; Beatty et al, 2003; Becker and Gerhart, 1996; Chadwick et al, 2012; Chaudhry et al, 2019; Combs et al, 2006; Huselid, 1995; Lawal and Ben-Bernard, 2014; Lin, 2012; MacDuffie 1995; Pfeffer and Veiga, 1999; Richey and Wally, 1998: 80; Stor and Haromszeki, 2020a). The organizational results may refer to efficiency, productivity, innovativeness, quality of products/services, and competitive advantage (Acosta-Prado et al, 2020; Arthur, 1994; Becker and Gerhart, 1996; Birdi et al, 2008; Easa and Orra, 2020; Ferguson and Reio, 2010; Huselid, 1995; Huselid et al, 1997; Paawe and Ferndale, 2017; Pfeffer and Veiga 1999; Sparrow et al, 2016; Stor and Haromszeki, 2020b). The research within the managerial results in most cases refers to the interrelations and levels of coherence between business strategies and particular subfunctions of HRM with company’s performance results (Beer et al, 1984; Bello-Pintado, 2015; Chanda and Shen, 2009; Dastmalchian et al, 2020; Jashari and Kutllovci, 2020; Guest, 1997; Guest et al, 2011; Schuler and Jackson, 1987; Stor and Suchodolski, 2016; Wright and Snell, 1991, 1995).…”
Section: The Theoretical Backgroundmentioning
confidence: 99%
“…The financial results are measured, for example, by means of market share, profits, sales, financial liquidity, share price, firm value and company’s goodwill (Arthur, 1994; Beatty et al, 2003; Becker and Gerhart, 1996; Chadwick et al, 2012; Chaudhry et al, 2019; Combs et al, 2006; Huselid, 1995; Lawal and Ben-Bernard, 2014; Lin, 2012; MacDuffie 1995; Pfeffer and Veiga, 1999; Richey and Wally, 1998: 80; Stor and Haromszeki, 2020a). The organizational results may refer to efficiency, productivity, innovativeness, quality of products/services, and competitive advantage (Acosta-Prado et al, 2020; Arthur, 1994; Becker and Gerhart, 1996; Birdi et al, 2008; Easa and Orra, 2020; Ferguson and Reio, 2010; Huselid, 1995; Huselid et al, 1997; Paawe and Ferndale, 2017; Pfeffer and Veiga 1999; Sparrow et al, 2016; Stor and Haromszeki, 2020b). The research within the managerial results in most cases refers to the interrelations and levels of coherence between business strategies and particular subfunctions of HRM with company’s performance results (Beer et al, 1984; Bello-Pintado, 2015; Chanda and Shen, 2009; Dastmalchian et al, 2020; Jashari and Kutllovci, 2020; Guest, 1997; Guest et al, 2011; Schuler and Jackson, 1987; Stor and Suchodolski, 2016; Wright and Snell, 1991, 1995).…”
Section: The Theoretical Backgroundmentioning
confidence: 99%
“…Consistent with this argument, an increased number of disciplines have perceived the understanding of the processes of innovation as a key concern. Human resource management (HRM) research has primarily focused on understanding the factors that can contribute to building innovative organizations [1][2][3]. Here, focus has predominantly been on top-down models, arguing that factors such as organizational climates [8] in which employees feel psychological empowered are key [9].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The aim of this chapter is to explore how different socio-cultural factors influence innovative capacities of individual inventors. When exploring innovation, the human research management literature have primarily focused on the management of organizations or organizational culture [1][2][3]. Meanwhile, individuals' background and upbringing is a theoretical and empirical blind spot, even though other disciplines, such as sociology and psychology, have shown that family and upbringing are key indicators of human and social capital known to be influential for individuals' general capacities [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Dengan demikian besaran koefisien regresi masing-masing faktor dapat dipercaya sebagaimana terlihat pada uji kausalitas di bawah ini: (Avianto, et al, 2019). Apabila aktivitas dari organisasi yang sebagian besar difokuskan untuk mengatur karyawan dan meyakinkan organisasi bahwa human resource dikerjakan untuk memenuhi tujuan organisasi dapat berjalan dengan efektif dan efisien hingga tujuan organisasi dapat tercapai, maka hal ini akan memberikan rasa puas tersendiri baik bagi manajerial perusahaan, maupun seluruh elemen karyawan (Easa & Orra, 2020).…”
Section: Pengujian Kausalitasunclassified